CD71 expressing circulating neutrophils serve as a novel prognostic biomarker for metastatic spread and reduced outcome in pancreatic ductal adenocarcinoma patients - Hansen, Frederik; Mittelstädt, Anke; Clausen, Finn-Niklas; Knoedler, Samuel; Knoedler, Leonard; Klöckner, Sebastian; Kuchenreuther, Isabelle; Mazurie de Keroualin, Johanne; Arnold, Lisa-Sophie; Anthuber, Anna; Jacobsen, Anne; Merkel, Susanne; et al. (Scientific Reports, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies, presenting a persisting global health burden. Neutrophils have a double-edged role in tumor progression exhibiting both pro-tumor and anti-tumor functions. CD71, also known as transferrin receptor 1, performs a critical role in cellular iron uptake and is highly expressed on proliferating cells, and especially on activated immune cells. CD71 is known to be elevated in various types of solid cancers and is associated with poor prognosis, however, the expression of CD71 on neutrophils in PDAC and its potential clinical impact is still unknown. Therefore, we analyzed CD71 on circulating neutrophils in PDAC and clinical control patients and found a significant increased expression in PDAC patients. High expression of CD71 on neutrophils in PDAC patients was associated with reduced outcome compared to low expression. CD71 on neutrophils correlated positively with the levels of proinflammatory cytokines IL-6, IFN-γ, and growth factor ligands CD40-L, and BAFF in plasma of PDAC patients. Finally, we have demonstrated that high expression of CD71 on neutrophils was also associated with an increased expression of CD39 and CD25 on circulating T-cells. Based on our findings, we hypothesize that CD71 on neutrophils is associated with tumor progression in PDAC. Further studies are required to investigate the distinct functionality of CD71 expressing neutrophils and their potential clinical application.
CRIS-Team Scopus Importer:2024-09-20
Keywords: CD71; Metastatic spread; Neutrophils; Pancreatic ductal adenocarcinoma; Prognostic biomarker; Transferrin receptor 1

Innate PD-L1 limits T cell-mediated adipose tissue inflammation and ameliorates diet-induced obesity - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; Elgendy, Amr; Elshafei, Moustafa; Heneghan, Helen M.; et al. (Science Translational Medicine, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.
CRIS-Team Scopus Importer:2022-03-25

Roboterassistierte viszeralchirurgische Eingriffe in Deutschland: Eine Analyse zum aktuellen Stand sowie zu Trends der letzten 5 Jahre anhand von StuDoQ|Robotik-Registerdaten - Brunner, Maximilian; Elgendy, Amr; Denz, Axel; Weber, Georg; Grützmann, Robert; Krautz, Christian (Die Chirurgie, 2023)
Robot-assisted systems have been increasingly used in general surgery for several years. Accordingly, the number of systems installed in Germany has also rapidly increased. While around 100 robot-assisted systems were used in German hospitals in 2018, this figure had already risen to more than 200 by 2022. The aim of this article is to present the current state of development and trends in robotic surgery in Germany. For this purpose, data from the StuDoQ|Robotics register were analyzed. Furthermore, a descriptive analysis of concomitant diagnosis-related groups (DRG) data was carried out via the Federal Statistical Office (Destatis), for a better assessment of the representativeness of the StuDoQ|Robotics register data. In both data sets, the annual number of robot-assisted visceral surgery procedures in Germany steadily increased. Compared to the DRG data, only 3.7% up to a maximum of 36.7% of all robot-assisted procedures performed were documented in the StuDoQ|Robotics register, depending on the type of procedure. Colorectal resections were the most frequent robot-assisted procedures (StuDoQ: 32.5% and 36.7% vs. DRG data: 24.2% and 29.7%) and had, for example, low mortality rates (StuDoQ: 1% and 1% vs. DRG data: 2.3% and 1.3%). Due to the low coverage rates of robot-assisted esophageal, gastric, pancreatic and liver interventions, no valid statements could be derived from the StuDoQ data for these areas. With the current coverage rates, the informative value of the StuDoQ|Robotics register is considerably limited for some types of intervention. In the future, measures should therefore be explored that lead to a significant increase in the coverage rates.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Hospital billing data; Robotic colorectal surgery; Robotic hepato-pancreato-biliary surgery; Robotic surgery of the upper gastrointestinal tract; StuDoQ register